Salivary metabolomics profile of patients with recurrent aphthous ulcer as revealed by liquid chromatography–tandem mass spectrometry. Issue 3 (March 2018) - Li, Yantao; Wang, Daoming; Zeng, Chunwei; Liu, Yichen; Huang, Guangyuan; Mei, Zhanlong
Objective: We compared the salivary nontargeted metabolite profiles between patients with recurrent aphthous ulcer (RAU) and healthy individuals to investigate the metabolic alterations associated with RAU. Methods: Saliva samples were collected from 45 patients with RAU and 49 healthy individuals, and the salivary metabolites were quantified using liquid chromatography–tandem mass spectrometry. The metabolomic profiles were then analyzed using multivariate and univariate statistical methods, and enrichment of the metabolites in various biological pathways was assessed. Results: In total, 206 significant differentiating metabolites (Wilcoxon test, false discovery rate [FDR] of <0.05) were identified between patients with RAU and healthy individuals. These metabolites were implicated in tryptophan metabolism, steroid hormone biosynthesis, and other metabolic pathways. Two commonly circulating steroids, estrone sulfate and dehydroepiandrosterone sulfate, were significantly lower in the saliva of patients with RAU (Wilcoxon test, FDR < 0.05, power > 0.9). Principal component analysis and partial least-squares discriminant analysis revealed metabolic perturbations involving RAU, and receiver operating characteristic curve analysis with several metabolites showed good diagnostic ability for RAU. Conclusions: The results of this study indicate that patients with RAU are characterized by metabolic imbalances. Psychogenic factors, endocrinopathies, and immunosuppression may contribute to the onset of RAU.